Social studies and the development of global citizens in educational systems - Kumpol Vongsatan (2020)
© 2020 Humanities, Arts and Social Sciences Studies. All rights reserved. Learning management in the 21st century should prepare students to be global citizens in an increasingly globalized world. Globalization is a process by which things change ever more rapidly and learners become increasingly interdependent upon one another. This is considered to be an important role of social studies teachers as core players in preparing the students to have the characteristics of global citizens by integrating a variety of experience with the learners. Therefore, the curriculum and learning activities should aim to develop the characteristics of global citizens for students and provide essential knowledge to them. It should also serve the learners' needs and help them develop social adjustment skills as well as learning skills. The learner should be able to seek knowledge by themselves and live with other people harmoniously leading to the characteristics of global citizenship. These are the important points to integrate into their learning activities in the instructions of social studies teachers. For this reason, the teaching methodology of social studies for global citizens is a mechanism that can be added to the curriculum and help learners develop their skills. The methodology consists of the teaching methodology to develop intellectual skills, thinking skills, life skills, and affective characteristics. As a result, learners will have an improved moral conscious, public awareness and the ability to peacefully live with other people as global citizens.